Network meta-analysis of treatment interventions for Helicobacter pylori infection in adult populations in East and Southeast Asia - Zhang, Li; Li, Bo-Ren; Guo, Si-Tong; Li, Yan (Frontiers in Pharmacology, 2024)
Background: Helicobacter pylori (H. pylori) infection poses a global health challenge, necessitating diverse treatment strategies. This network meta-analysis aimed to assess various treatment regimens for H. pylori in East and Southeast Asian populations.: A systematic search was conducted in PubMed, Embase, and the Cochrane Library databases from inception to Dec 20, 2023, to identify relevant randomized controlled trials (RCTs) on H. pylori treatment interventions in East Asian and Southeast Asian populations. The primary outcome focused on effectiveness, specifically the rate of H. pylori eradication, while the secondary outcome evaluated overall safety, including the incidence of total and serious adverse effects. Network geometry plots were generated to illustrate direct and indirect treatment comparisons, using triple therapy (TT) as the reference standard. Odds Ratios (ORs) and 95% confidence intervals (CIs) were calculated using random-effects models to account for study heterogeneity and consistency models for indirect comparisons. The treatment hierarchy was assessed using the ranking probabilities and surface under the cumulative ranking curve (SUCRA) values. Results: 79 studies met the inclusion criteria, with 99 paired comparisons. The included studies, conducted in Southeast Asia and among East Asian populations, included 29,903 patients. Significant outcomes in treat effectiveness were observed in various comparisons, such as sequential therapy vs. TT, bismuth quadruple therapy (BQT) vs. TT, high-dose dual therapy (HDDT) vs. TT, concomitant therapy vs. TT, P-CAB-based therapy vs. TT, and R-HT/HT vs. TT. R-HT/HT was the top choice based on rankograms and SUCRA values (SUCRA=96.5). Regarding overall safety, significant results were noted in comparisons involving BQT, HDDT, concomitant therapy, sequential therapy, and P-CAB-based therapy. HDDT achieved the highest overall safety based on rankograms and SUCRA values (SUCRA=0.0). HDDT demonstrated the lowest incidence of serious adverse events, according to global rankograms and SUCRA values (SUCRA=19.7).This network meta-analysis highlights the complexity of treating H. pylori in East and Southeast Asia. R-HT/HT emerged as the most effective regimen, while HDDT proved to be the safest, with the lowest incidence of serious adverse events. These findings are crucial for optimizing treatment protocols in these regions.